Self-help group pada remaja dengan internet gaming disorder - Masayu Nandhia Dwiputri (Universitas Muhammadiyah Malang, 2023)
Internet Gaming Disorder refers to persistent and repeated involvement in video games that leads to clinically significant impairment or distress as demonstrated by five (or more) of the nine criteria over a 12-month period. The purpose of this study was to reduce the intensity of using mobile phones to play online games on teenage clients. The subjects in this study were four male adolescent subjects aged 13-15 years. The assessment methods used were clinical interviews, observations, graphic tests (BAUM, DAP (draw a person) and HTP (house tree person)) and the Game Addiction Scale (GAS). The intervention technique used was a self-help group. The results of the intervention showed a decrease in the intensity of using mobile phones to play online games. Internet gaming disorder mengacu pada keterlibatan terus-menerus dan berulang dalam video game yang menyebabkan gangguan atau tekanan yang signifikan secara klinis seperti yang ditunjukkan oleh lima (atau lebih) dari sembilan kriteria selama periode 12 bulan. Tujuan dari penelitian ini adalah untuk mengurangi intensitas penggunaan telepon seluler untuk bermain game online pada klien remaja. Subjek dalam penelitian ini adalah empat orang subjek remaja laki-laki berusia 13-15 tahun. Metode penilaian yang digunakan adalah wawancara klinis, observasi, tes grafis (BAUM, DAP (menggambar orang) dan HTP (rumah pohon)) dan Game Addiction Scale (GAS). Teknik intervensi yang digunakan adalah self-help group. Hasil intervensi menunjukkan adanya penurunan intensitas penggunaan ponsel untuk bermain game online.